2018
DOI: 10.1016/j.ijcard.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a clinical risk score to predict the response to cardiac resynchronization therapy

Abstract: The ScREEN score (Sex category, Renal function, ECG/QRS width, Ejection fraction and NYHA class) is composed of widely validated, easy to obtain predictors of CRT response, and predicts CRT response and overall mortality. It should be helpful in facilitating early consideration of alternative therapies for predicted non-responders to CRT therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 32 publications
1
36
0
4
Order By: Relevance
“…Since not every heart failure patient seems to benefit from CRT, major efforts have been made to identify predictors for CRT response. Recently, a simple risk score has been derived from a French multi-centre cohort and then validated in four high-volume European centres [15]. CRT response was defined as an improvement of !1 NYHA functional class and/or !5% left ventricular ejection fraction (LVEF) in the absence of hospitalization for congestive heart failure within the 12 months after implant.…”
Section: Traditional Determinants Of Crt Responsementioning
confidence: 99%
“…Since not every heart failure patient seems to benefit from CRT, major efforts have been made to identify predictors for CRT response. Recently, a simple risk score has been derived from a French multi-centre cohort and then validated in four high-volume European centres [15]. CRT response was defined as an improvement of !1 NYHA functional class and/or !5% left ventricular ejection fraction (LVEF) in the absence of hospitalization for congestive heart failure within the 12 months after implant.…”
Section: Traditional Determinants Of Crt Responsementioning
confidence: 99%
“…We reported here for the first time that NYHA class ≥III at the time of implantation was associated with CRT response in the ≥75-year-old individuals but not in younger patients. Conversely, a recent study showed that NYHA class ≤III was an independent predictor of CRT benefit in a mid-sixties population [20]. In contrast, AF has been associated with poor results of CRT [21].…”
Section: Discussionmentioning
confidence: 96%
“…Over the past decades, prior risk models [9, 10, 14-16] were derived with good calibration and accuracy in derivation cohorts or Western validation cohorts; however, Asian populations, especially Chinese participants, are rarely used for validation [17]. VALID-CRT [11]and sex category, renal function, ECG/QRS width, ejection fraction, and NYHA class (ScREEN) [8] scores were derived and validated in European multicenter studies, and ejection fraction, atrial fibrillation, age, renal function, and NYHA class (EARRN) [10] does not have a validation population.…”
Section: The Published Scoresmentioning
confidence: 99%